GENESIS AND COMPOSITION OF COARSE-CLASTIC MATERIAL OF THE KEMENSKAYA GROUP, UDOKAN COMPLEX, EASTERN SIBERIA - Burmistrov V.N. (My University, 1989)
The Udokan complex, whose deposits are exposed in the Udokan Range, in the Kalar Range and in the Kodar Massif in the southwestern part of the Aldan shield, traditionally has attracted attention because it is the Proterozoic parastratotype and has economic copper potential. From the results of 86 chemical analyses and using the generally accepted classification, we were able to identify the plutonic and extrusive rock families and species. Average compositions of the most common rocks are given. The volcaniclastic strata of the Padra group are intruded by numerous bodies of granite porphyry and granophyric, alaskitic and aplitic granite (Padora complex), which in external appearance, texture and composition resemble the granitoid rock pebbles from the puddingstone horizon. Although further work is needed for a more objective identification of the rock fragments studied, we can already consider the rock associations of the Padra group and Padora complex to be the most likely sources of the clastic material for the Kemenka sedimentary basin, without, of course, ruling out additional supply from basement rocks.
Keywords: Proterozoic; Precambrian::Proterozoic; Докембрий::Протерозой